Fast pyrolysis of empty fruit bunch and palm kernel shell for production of bio-oil using auger reactor / Nurul Suhada Ab Rasid - Ab Rasid, Nurul Suhada (Institute of Graduate Studies, UiTM, 2017)
Pyrolysis has received a lot of interest as it can convert biomass into gas, liquid (bio-oil) and solid products. Bio-oil can be utilized as a feedstock for various chemicals as well as fuels production, and heat and power generations. The purpose of this research is to optimize the process conditions for bio-oil production from oil palm empty fruit bunch (EFB) and palm kernel shell (PKS) in an auger reactor and to elucidate the detailed characteristics of bio-oil. The maximum bio-oil yield for EFB was 64.54 wt% at temperature of 500 oC, nitrogen flow rate of 2 L/min and mass feeding of 8 kg/hr, while the maximum of 64.38 wt% of bio-oil yield was obtained at temperature of 550 oC, nitrogen flow rate of 3 L/min and 8 kg/hr for PKS. The highest higher heating value obtained for both EFB and PKS bio-oil was 27.28 kJ/mol and 26.68 kJ/ mol, respectively, for bio-oil produced at 550 oC. The moisture content observed to be reduced with increasing pyrolysis temperature.